Contribution of bread and biscuits to vitamin A daily requirement of preschool children in Lagos State, Nigeria - Uchendu, Florence N.; Oyewole, Oyediran Emmanuel (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Introduction and aim. Vitamin-A-deficiency is a public health problem among preschool children of Nigeria. Study determined the contribution of bread and biscuits to vitamin A-daily-requirement of preschool children in Lagos-State, Nigeria. Material and methods. A community-based-study using a cross-sectional-design with analytical component was carried out from 2013-2015. Multi-stage-sampling-technique was used to select mothers of preschool-children (n=1599) in 5 Local-Government- Areas of Lagos. Respondents’ socio-demographic information and samples consumption-pattern were collected using validated, food-frequency-questionnaire/dietary recall. Retinyl palmitate content of randomly selected commonly-consumed brands of oven-fresh-bread stored for 5-days and biscuits (30- to 60-days) at prevailing outdoor-market-temperatures were analysed using High-Performance-Liquid-Chromatography. Contribution to preschool children’s vitamin A-daily-requirements were determined. Data were analysed using Student’s t-test and ANOVA at p<0.05. Results. Mean age of preschool children was 31.44±5.28 months. Mean intakes of samples were bread (117.6 ±15.9 g/d) and biscuits (59.8±27.9 g/d). Range of contribution to vitamin-A-daily-requirement of preschool-children was 0-178.4 %. Samples contribution to vitamin A-daily-requirement of pre-school-children were oven-fresh bread (68.3 %); 5 days bread (20.7%); 30-days biscuits (25.0%) and 60-days biscuits (6.8%). Overall contribution to vitamin A-daily-requirement were bread (51.4%) and biscuits (22.4%). Statistically significant difference existed between samples contribution and vitamin-A-daily-requirement of preschool children. Conclusion. Bread and biscuits samples contributed significantly to the vitamin-A-daily-requirement of preschool children.
Keywords: biscuits; bread; vitamin A daily requirement